2020
DOI: 10.1021/acsomega.0c03496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electric Potential Gradient on Methane Adsorption and Desorption Behaviors in Lean Coal by Electrochemical Modification: Implications for Coalbed Methane Development of Dongqu Mining, China

Abstract: The application of electrochemical modification for accelerating methane extraction in lean coal seams is limited due to the lack of experimental and theoretical research studies. Therefore, electrochemical modification with different electric potential gradient values was selected to modify lean coals in this study; meanwhile, the amount of methane adsorption and the methane desorption ratio were tested and analyzed. The results showed that the maximum amount of methane adsorption in coal samples decreased af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The greater the burial depth of the coal seam, the larger the in-situ stress and the greater the distance of gas escape, which is also conducive to gas sealing. The greater the thickness of the coal seam, the more conducive it is to gas preservation (Lu et al 2018b;Kang et al 2020;Li et al 2020b). However, some studies have shown that the depth effect is no longer obvious when the depth of coal seam exceeds the critical point of 800-900 m (Li et al 2020a).…”
Section: Understanding Of Coal Seam Gas Occurrence Characteristicsmentioning
confidence: 99%
“…The greater the burial depth of the coal seam, the larger the in-situ stress and the greater the distance of gas escape, which is also conducive to gas sealing. The greater the thickness of the coal seam, the more conducive it is to gas preservation (Lu et al 2018b;Kang et al 2020;Li et al 2020b). However, some studies have shown that the depth effect is no longer obvious when the depth of coal seam exceeds the critical point of 800-900 m (Li et al 2020a).…”
Section: Understanding Of Coal Seam Gas Occurrence Characteristicsmentioning
confidence: 99%
“…Methods other than CO 2 substitution and N 2 displacement will have a significant effect on reservoir permeability . One approach is fluid injection, which includes hydraulic, high energy gas, , supercritical CO 2 , , liquid nitrogen, and steam injection fracturing. , Another approach is the application of external acoustic, electric, electromagnetic, or electrochemical fields. Although these methods have achieved enhancements, there are still some limitations, such as water locking damage, construction costs, complex operations, ecological environmental pollution, and even the possibility of inducing earthquakes by hydraulic fracturing. , At present, microwave modification technology has been successfully used for coking, , reduction of energy for pulverization, lignite dehydration, coal desulfurization, low-rank coal pyrolysis, biomass pyrolysis, enhancing floatation, auxiliary rock breaking, heavy oil exploitation, and oil shale exploitation …”
Section: Introductionmentioning
confidence: 99%
“…Mirzaei et al studied the adsorption of methane in active carbons with/without surface functional groups by doping heteroatoms into the carbon framework, finding that the strong electronegative O atom in the functional groups repels the electronegative C atom in the CH 4 molecule . Yu et al, Han et al, and Kang et al also found that the types and proportions of surface groups are closely related to the methane adsorption capabilities in coals.…”
Section: Introductionmentioning
confidence: 99%